Desenvolvimento de uma plataforma aberta de robô móvel para propósitos gerais - Matsumura, Takao [UNESP] (2014)
The research on mobile robots has been driven by technological advance. There are re-search fronts on different aspects and challenges of mobile robots, among which are top-ics such as locomotion, navigation and control architectures. This growth in research also leads a greater need for mobile bases, in other words, for mobile robot platforms for gen-eral purposes, destined for research and educational purposes. This situation is applica-ble to the Laboratory of Evolutionary Automation and Computation of IBILCE, Unesp Campus of São José do Rio Preto. This work presents the development of a low cost mobile robot platform with an open hardware, software and control architecture, intended for general purposes. The platform aims at facilitating and flexibilizing the development process of robotic applications and studies through a simplified communication interface and abstracting the heterogeneity of the peripheral hardware devices. This platform is able to offer greater freedom in relation to programming languages, control paradigms, development environments of its control software, extending to the technological control devices